Pengembangan Media Pembelajaran Berbasis Video Animasi Menggunakan Aplikasi Canva pada Siswa Kelas VII MTS Miftahul Huda Karangsono Ngunut Tulungagung - Liza Nur Khoiru Nikmah (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to produce animated video based learning media using the Canva application for class VII students of mts Miftahul Huda Karangsono Ngunut Tulungagung. Development is an effort carried out systematically to produce products toimprove skills and insights. Animated video learning media functions as a tool in the learning process that is intended to convey messages and can prooke students thoughts feelings and desires to learn. Canva is an alternative graphic desaign media that can be used in creating learning materials to create a more interesting and enjoyable learning process. The research uses research and development methods (Research and Development) with the ADDIE model. The subjects of the study were students of class VII MTs Miftahul Huda Karangsono Ngunut Tulungagung. Data collection techniques are feasibility data which includes validity, practicality, and effectiveness. Data analysis techniques include student needs analysis techniques, media feasibility, validity, practicality and media effectiveness. The results of research and development of animated video based learning media using the canva application showed positive result, the media was declared suitable for use. Based on the validity of media experts (80%) and material ezperts (96,1%), the media was also declared practical by teachers with questionnaire and observation results of (90%) and (87,5%). In terms of effectiveness, the media was able to improve student learning outcomes with classical completeness of 83,3% (small scale) and 85,71% (large scale), and received a positive response from students with a percentage of (92,4%) and (86,38%). Thus, the development of animated video based learning media using the canva application has proven to be feasible for use in the learning process. The validation results from media and material experts show a high level of validity, while the reesults of observations and questionnaires show that this media is practical for teachers to use and interesting for students. In addition, the effectiveness of the media is shown through increased student learning outcomes and high positive responses. Therefore, the development of animated video based learning media using the canva application can be an alternative in delivering material, especially in social studies subjects in class VII MTs.